2010
DOI: 10.1111/j.1752-1688.2010.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Stream Shade: Riparian Buffer Height and Density as Important as Buffer Width1

Abstract: DeWalle, David R., 2010. Modeling Stream Shade: Riparian Buffer Height and Density as Important as Buffer Width. Journal of the American Water Resources Association (JAWRA) 46(2):323‐333. DOI: 10.1111/j.1752‐1688.2010.00423.x Abstract:  A theoretical model was developed to explore impacts of varying buffer zone characteristics on shading of small streams using a path‐length form of Beer’s law to represent the transmission of direct beam solar radiation through vegetation. Impacts of varying buffer zone height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…Tree density is often overlooked when evaluating nutrient and greenhouse gas dynamics in riparian forests. However, tree density plays a crucial role in understanding riparian forest function including nutrient input via litter fall, nutrient uptake, and shading of the forest floor (DeWalle, 2010). For example, Spies and Franklin (1991) found that young (40 yr) Douglas fir [ Pseudotsuga menziesii (Mirb.)…”
Section: Discussionmentioning
confidence: 99%
“…Tree density is often overlooked when evaluating nutrient and greenhouse gas dynamics in riparian forests. However, tree density plays a crucial role in understanding riparian forest function including nutrient input via litter fall, nutrient uptake, and shading of the forest floor (DeWalle, 2010). For example, Spies and Franklin (1991) found that young (40 yr) Douglas fir [ Pseudotsuga menziesii (Mirb.)…”
Section: Discussionmentioning
confidence: 99%
“…These are the parameters most commonly studied concerning global radiation reduction (Zwieniecki and Newton, 1999;DeWalle, 2010;Sridhar et al, 2004) but there are no clear results concerning the ranked importance of these. The VSI results in a significant correlation which had the same or even better correlation coefficients with WT as the individual vegetation parameters.…”
Section: Vsi and Its Spatial Scale In Terms Of Water Temperaturementioning
confidence: 99%
“…For each 50 m cross-section, VSI was calculated that integrates the parameters vegetation height (h R ), vegetation width (w), and vegetation density (d), as these parameters were found to influence water temperature (WT) most (DeWalle, 2010;Holzapfel et al, 2013). For the VSI of a northwards or southwards flowing river, all vegetation parameters were calculated as mean values of the orographic left and right river bank.…”
Section: Vegetation-shading Index (Vsi)mentioning
confidence: 99%
See 2 more Smart Citations